Analytical modeling of CV and I-V characteristics in p-GaN gate HEMTs based on the unified 2DEG density expression - Zhang, Lili; Yin, Yanan; Qiu, Yiwu; Wang, Tao; Zhang, Pingwei; Zhou, Xinjie (Microelectronics and reliability, 2025)
This work proposes a physics-based analytical model for p-GaN gate high electron mobility transistors (HEMTs), developed through a self-consistent solution of the Schrödinger-Poisson equations. The model explicitly accounts for voltage distribution across the device, focusing on voltage drops across the metal/p-GaN Schottky junction and the AlGaN barrier layer. A comprehensive analysis is conducted to evaluate the impact of several factors on the electrical characteristics of p-GaN gate HEMTs. The investigated factors include the net polarization charge density at the AlGaN/GaN interface, out-diffused Mg acceptor density in the AlGaN barrier, and depletion charge density in the unintentionally doped GaN (UID-GaN) buffer layer. Furthermore, a unified expression for the two-dimensional electron gas (2DEG) charge density is derived, which is valid across all operation regions. On this basis, expressions for gate capacitance and drain current are developed. The model's credibility is validated by the agreement between modeled and measured CV and I-V characteristics across three p-GaN gate HEMT samples. •Establishment of an analytical model for p-GaN gate high electron mobility transistor•Development of a unified expression for the 2DEG charge density•Derivation of expressions for the drain current and gate capacitance•Credibility verification of the model by comparison with the experimental data